2021
DOI: 10.2196/32005
|View full text |Cite
|
Sign up to set email alerts
|

Medical Needs Extraction for Breast Cancer Patients from Question and Answer Services: Natural Language Processing-Based Approach

Abstract: Background A large number of patient narratives are available on various web services. As for web question and answer services, patient questions often relate to medical needs, and we expect these questions to provide clues for a better understanding of patients’ medical needs. Objective This study aimed to extract patients’ needs and classify them into thematic categories. Clarifying patient needs is the first step in solving social issues that patient… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…The second and third are “mammogram” and “pap test,” screening tests for breast cancer and cervical cancer, respectively. We chose cancer screening as an illustrative case as these are common cancer types that are often discussed on social media [ 3 , 55 ] such that research would benefit from identifying relevant content that does not explicitly mention these technical, formal screening tests.…”
Section: Resultsmentioning
confidence: 99%
“…The second and third are “mammogram” and “pap test,” screening tests for breast cancer and cervical cancer, respectively. We chose cancer screening as an illustrative case as these are common cancer types that are often discussed on social media [ 3 , 55 ] such that research would benefit from identifying relevant content that does not explicitly mention these technical, formal screening tests.…”
Section: Resultsmentioning
confidence: 99%
“…Then the generated feature maps F2, F3, and F4 are upsampled to the size of F1 for concatenation. For extracting the global context information from various levels of feature maps, four dilated convolutions (AT conv 1, AT conv 2, AT conv 3, AT conv 4) [20] with various atrous rates (2,4,8,16) are employed in a parallel fashion. Finally, a convolution operation is applied to obtain the final feature map.…”
Section: B Scr Modulementioning
confidence: 99%
“…According to [3], the average misdetection rate among medical professionals is around 30%. In a recent survey [4], it was found that misdetection of breast cancer from mammograms is the main cause of legal suits against medical professionals. To overcome the above mention misdetection, computer-aided detection (CAD) systems have been developed by researchers to reduce false detection.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, for diabetes patients, social support categories identified in users' posts showed that they are most interested in achievement, congratulations, network support, seeking emotional support, seeking informational support and so on [18]. For critical diseases, a text mining study showed that worrying about cancer with subjective symptoms occurs most frequently among all breast cancer patient posts [19]. A qualitative study summarized information needs of individuals who have sexually transmitted infections in a web-based forums of the American Sexual Health Association, which found that psychosocial information need should be caught more attention [20].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Through manual labeling of the replies, the study found that most community users received effective responses to their information needs, which mainly took the form of answers, discussions, inquiries, and emotional support. Previous research has summarized the types of feedback as answers, inquiries, and emotional support [19]. This study identified a new form of feedback, namely, discussion, which not only provided more comprehensive supplementary information to the inquirer but also promoted communication among community users, thus increasing community activity.…”
Section: Plos Onementioning
confidence: 99%